Pelatihan Dan Bimbingan Penulisan Artikel Ilmiah Mahasiswa PGSD UNU NTB - Azmussya’ni, Azmussya’ni; Lalu Abdul Aziz; Husaen Sudrajat; Qamariah (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2024)
The purpose of this community service activity is to provide knowledge and understanding of how to write scientific papers in scientific journals, produce scientific papers in the form of manuscripts/articles to be published in scientific journals and productivity and development of writing skill in scientific articles. The target audience for this service is UNU NTB students who are preparing or have prepared a thesis. The method of this activity is one day of training on writing scientific papers in the first week and one days of guidance on writing scientific papers in the second week. The results of this service showed a significant increase in students' understanding and skills in writing scientific articles, through development of writing skill in scientific articles and productivity in journal writing.